2019
DOI: 10.1186/s12939-019-0947-9
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and newborn health needs for women with walking disabilities; “the twists and turns”: a case study in Kibuku District Uganda

Abstract: Background In Uganda 13% of persons have at least one form of disability. The United Nations’ Convention on the Rights of Persons with Disabilities guarantees persons with disabilities the same level of right to access quality and affordable healthcare as persons without disability. Understanding the needs of women with walking disabilities is key in formulating flexible, acceptable and responsive health systems to their needs and hence to improve their access to care. This study therefore explore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 41 publications
1
20
0
3
Order By: Relevance
“…Table 1 presents the characteristics of the eligible studies. Of the 26 eligible studies, 19 were qualitative in design [7,10,11,[18][19][20][31][32][33][34][35][36][37][38][39][40][41][42][43]; four used a survey design [44][45][46][47]; and three used mixed methods design [48][49][50]. The 26 studies were reported from twelve African countries: Uganda (seven studies) [7,10,31,32,34,37,39];…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 presents the characteristics of the eligible studies. Of the 26 eligible studies, 19 were qualitative in design [7,10,11,[18][19][20][31][32][33][34][35][36][37][38][39][40][41][42][43]; four used a survey design [44][45][46][47]; and three used mixed methods design [48][49][50]. The 26 studies were reported from twelve African countries: Uganda (seven studies) [7,10,31,32,34,37,39];…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Lastly, two main economic barriers emerged from review of eligible studies. These included unaffordability of SRH services and information [18,37,49,54]; and general financial and resource poverty which hinder PWDs' access to SRH services and information [7,20,31,32,35,38,51].…”
Section: Synthesis Of Barriers To Srh Services Among Pwdsmentioning
confidence: 99%
“…For many of the WWDs in our study, pregnancy and childbearing reaffirmed their feminine identity and sexuality as well as their self-worth as women. In previous studies, WWDs have commented on how becoming pregnant was experienced as an important achievement and affirmation of femininity, and how the experience of pregnancy confirmed that their biological bodies could function like those of women without disabilities [ 49 ]. Our findings particularly showed that being a mother and doing mothering were fulfilling life events for many WWDs - events that caused them (and others) to realize their abilities rather than disabilities [ 46 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, WWDs have commented on how becoming pregnant was experienced as an important achievement and affirmation of femininity, and how the experience of pregnancy confirmed that their biological bodies could function like those of women without disabilities [ 49 ]. Our findings particularly showed that being a mother and doing mothering were fulfilling life events for many WWDs - events that caused them (and others) to realize their abilities rather than disabilities [ 46 , 49 ]. As the pronatalist orientation of our research context have tended to encourage childbearing among women as a marker of biological and social accomplishments, we are not surprised that many of our participants viewed childbearing as a means to self-actualisation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation